Study and Handling of Violence Against Women and Children in the Larantuka Community - Erni R. Klau; Mariana I. R. D. Pareira; Ambara S. Mardani; Gallex Simbolon; Samrid Neonufa; Angela R. Napa; Maria G. Vigeista (Global Writing Academica Researching & Publishing, 2023)
Women and children are increasingly vulnerable to discrimination and violence due to gender inequality. It is the current phenomenon that is happening in Larantuka communities. The dominant forms of violence against women in the domestic domain occuring in Larantuka City are predominantly physical violence and household neglect. This research aims to explore the cases of violence against women and children to examine the handling efforts by government institutions. The phenomenological approach was delivered using in-depth interviews with 6 (six) Key Informant Interviews (KII) from Government Institutions who handle the cases of violence i.e. DP2KBP3A, a Social Worker, The Head of the East Flores Police Women and Children Protection Unit, 5 (five) housewives, and 8 (eight) teenagers (≤ 18 years) through Focus Group Discussion (FGD). The findings of this study are a significant increase in cases of violence. Data from the East Flores Police Women and Children Protection Unit in 2022 shows 67 cases were recorded. In recent year between January-June 2023, 61 case recorded shows dominant cases are sexual and domestic violence. The majority victims of these cases are women and underage children (minors). The causes are the abandonment of children due to parents leaving abroad for work, permissive parenting, and high respect for customs.